Regenerasi Empat Genotipe Gandum (Triticum aestivum L.) Pasca Transformasi Melalui Agrobacterium tumefaciens - Apriana, Aniversari; Sisharmini, Atmitri; Fitriyani, Fitriyani; Sustiprijatno, Sustiprijatno (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2014)
Genetic transformation ofwheat mediated by Agrobacterium tumefaciens has notbeen established yet. This research aimed to obtain themost responsive wheat genotype to be transformed, toselect the most effective combination of growth regulator forregenerating transforman calli, and to determine thetransformation efficiency. Transformation mediated by A.tumefaciens was performed on four genotypes of wheat,namely Combi, Fasan, Perdix, and Naxos-Wew.Transformed calli with green spots in selection media weretransferred to regeneration media containing 25 mg/lhygromycin, i.e. R1H25 and R2H25. The obtained plantletswere analyzed by PCR using specific primers for hygromycinphosphotransferase gene. The results showed that Fasanwas the most responsive genotype in callus formation(95.47%) and regeneration both in R1H25 (27%) and R2H25(28.6%) media. Fourteen plantlets were succesfullyacclimatized and PCR analysis showed that there were fourpositive transformants containing the hpt gene. The resultsare expected to provide information on the development oftransgenic wheat in Indonesia, specifically in the success ofcallus formation and regeneration of wheat aftertransformation using A. tumefaciens.